Food safety assessments of acrylamide formation and characterizations of flaky rolls enriched with black rice (Oryza sativa) - Lu, Wen-Chien; Cheng, Yu-Tsung; Chan, Yung-Jia; Li, Po-Hsien (Frontiers in Nutrition, 2022)
This study aims to investigate the physicochemical composition, textural parameters, and chemical constituent of flaky rolls incorporated with different proportions of black rice flour. According to farinographic characteristics, the addition of black rice flour could reduce the stability and increase the dough development time and water absorption (%). While for the extensographic properties, addition of black rice flour resulted in significantly different maximum resistance to extension (BU) and extensibility (cm) vs. the control. With the addition of black rice flour in flaky rolls, the crude protein, total dietary fiber (TDF), soluble dietary fiber (SDF), and insoluble dietary fiber (IDF) were significantly improved. Glucose released was much lower with 10 and 20% black rice than the control and 5% black rice because of the higher black rice inclusion. With increasing black rice incorporation, total anthocyanin content, and antioxidant capacity was also improved. The content of asparagine, acrylamide, hydroxymethylfurfural (HMF), furfural, methylglyoxal, and glyoxal in flaky rolls was also increased. The proper content of black rice flour (5%) could significantly enhance the stability of the dough properties; control the final volume, texture, and appearance; and retain good protein and fiber composition, antioxidant capacity, and overall acceptance of the flaky roll.